2023
DOI: 10.1021/acs.jcim.2c01459
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Description of the Content Variation of Natural Products (NPs): To Prompt the Yield of High-Value NPs and the Discovery of New Therapeutics

Abstract: Natural products (NPs) have long been associated with human production and play a key role in the survival of species. Significant variations in NP content may severely affect the "return on investment" of NP-based industries and render ecological systems vulnerable. Thus, it is crucial to construct a platform that relates variations in NP content to their corresponding mechanisms. In this study, a publicly accessible online platform, NPcVar (http://npcvar.idrblab.net/), was developed, which systematically des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…To provide more comprehensive information, we also collected data on the host plants of endophyte, the plant parts from which these endophytes were isolated, and the geographic information of the host plants. Moreover, we collected data on the content of different NPs produced by these endophytes under various fermentation conditions, which are also available in NPASS 2.0 and NPcVar [ 36 ].…”
Section: Construction and Contentmentioning
confidence: 99%
“…To provide more comprehensive information, we also collected data on the host plants of endophyte, the plant parts from which these endophytes were isolated, and the geographic information of the host plants. Moreover, we collected data on the content of different NPs produced by these endophytes under various fermentation conditions, which are also available in NPASS 2.0 and NPcVar [ 36 ].…”
Section: Construction and Contentmentioning
confidence: 99%
“…The content of natural products is affected by various factors. Recently, research found that the content of the same natural product can vary under different conditions, such as molecular regulation, species factor, environmental condition and combined factors ( 17–19 ). In the evolutionary formation of natural products, there are characteristics of convergent evolution ( 20 ).…”
Section: Introductionmentioning
confidence: 99%